2021
DOI: 10.1016/j.jhin.2021.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of SARS-CoV-2 among healthcare workers and patients in a teaching hospital in the Netherlands confirmed by whole-genome sequencing

Abstract: We investigated the sources of infection among healthcare workers (HCWs) and patients in a teaching hospital during the early stages of the COVID-19 pandemic with epidemiological and whole genome sequencing data. This retrospective study is performed in a Dutch teaching hospital with nursing facilities located in Rotterdam and Schiedam with around 45,000 admissions per year. From 3 rd April to 11 th May 2020 88 HCWs and 215 patients were diagnosed with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 15 publications
4
39
0
1
Order By: Relevance
“…[3][4][5] However, in the setting of widespread community transmission, sequencing of SARS-CoV-2 is essential as an adjunct to contact tracing to confirm transmission among personnel. 6,9 In the current investigation, sequencing confirmed transmission of SARS-CoV-2 among emergency department personnel but demonstrated that the suspected 6-person outbreak included 2 distinct transmission clusters and 1 unrelated infection. Our results suggest that SARS-CoV-2 variants initially acquired in the community were subsequently spread among hospital personnel.…”
Section: Discussionmentioning
confidence: 56%
“…[3][4][5] However, in the setting of widespread community transmission, sequencing of SARS-CoV-2 is essential as an adjunct to contact tracing to confirm transmission among personnel. 6,9 In the current investigation, sequencing confirmed transmission of SARS-CoV-2 among emergency department personnel but demonstrated that the suspected 6-person outbreak included 2 distinct transmission clusters and 1 unrelated infection. Our results suggest that SARS-CoV-2 variants initially acquired in the community were subsequently spread among hospital personnel.…”
Section: Discussionmentioning
confidence: 56%
“…Through the employment portable sequencing instruments and rigging an online integrative analysis platform, the protocols, primers and bioinformatics tools devised by the ARTIC network allow for realtime epidemiology of the SARS-CoV-2 outbreak. Yet, only a few studies have been published in which whole genome sequencing (WGS) has been combined with epidemiological data to trace possible transmission chains in health care settings [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The study authors also emphasized the role of prevention efforts in shaping these outcomes. (Seidelman, et al 2020, Paltansing, et al 2021. Yale University's Emergency Department described "structure[ing] into distinct pods...staggering breaks or using portable computers…taping off or removing chairs" and "individually packaged meals" (Sangal, et al 2020 Although households likely did not implement many of the prevention protocols cited in Table 2, they did reduce their geographic mobility (Chetty, et al 2020).…”
Section: Large-group Prevention Activities and Their Possible Efficacymentioning
confidence: 99%
“…If this unknown category were allocated proportionally between community-and work-acquired, the ratios shown in my Figure 3 would not change. 18 Another study of a hospital in the Netherlands (Paltansing, et al 2021) measured in-hospital transmission using whole-genome sequencing. It found only one in-hospital transmission after April 30, 2020, which was the seventh day after implementing universal masking of healthcare workers.…”
Section: Ivb Employees Of Duke Health and Meat Processors Before And After Prevention Protocolsmentioning
confidence: 99%